Microsatellites for butterfly conservation: historical challenges, current relevance, and a guide to implementation - Heffernan, Emily; Barkdull, Megan; Brady, Noah (Frontiers in Ecology and Evolution, 2024)
We are nearing the 20-year anniversary of a groundbreaking paper which details how microsatellite marker development in Lepidoptera is "extremely difficult for no apparent reason."How far have we come in these past 20 years? Microsatellites are still the marker of choice in many population genetics studies for their ease of use, high degrees of polymorphism, speciesspecificity, and low cost. The rise of next-generation sequencing technologies (e.g., 454, Illumina, PacBio, etc.) has greatly advanced our abilities to generate many microsatellite markers per species. In this paper, we summarize the improvements in marker development using next-generation technology. Using case studies, we review the use and implementation of microsatellite markers in different conservation programs. Lastly, we provide a guide to data interpretation of microsatellite data generated for butterflies, with the goal of supporting student researchers and conservation practitioners in evaluating the meaning in their data.